2022
DOI: 10.3390/cancers14174108
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumoral Effect of Chemerin on Ovarian Cancer Cell Lines Mediated by Activation of Interferon Alpha Response

Abstract: The pleiotropic adipokine chemerin affects tumor growth primarily as anti-tumoral chemoattractant inducing immunocyte recruitment. However, little is known about its effect on ovarian adenocarcinoma. In this study, we examined chemerin actions on ovarian cancer cell lines in vitro and intended to elucidate involved cell signaling mechanisms. Employing three ovarian cancer cell lines, we observed differentially pronounced effects of this adipokine. Treatment with chemerin (huChem-157) significantly reduced OVCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…It is regarded as a putative tumor suppressor gene since it is one of the frequently methylated locations in different malignancies 28,29 . IFI27 (Interferon alpha‐inducible protein 27), initially reported to mediate interferon (IFN)‐induced cell death, has recently been shown to influence cell cycle regulation, preventing cancer cells from proliferating while avoiding cell apoptosis 30 . As our multifactor Cox regression analysis results suggest, IFI27 is a patient protective factor.…”
Section: Discussionmentioning
confidence: 75%
“…It is regarded as a putative tumor suppressor gene since it is one of the frequently methylated locations in different malignancies 28,29 . IFI27 (Interferon alpha‐inducible protein 27), initially reported to mediate interferon (IFN)‐induced cell death, has recently been shown to influence cell cycle regulation, preventing cancer cells from proliferating while avoiding cell apoptosis 30 . As our multifactor Cox regression analysis results suggest, IFI27 is a patient protective factor.…”
Section: Discussionmentioning
confidence: 75%
“…Hoffmann et al [ 251 ], based on their study, concluded that the use of exogenous chemerin has no effect on both ovarian cancer cells and physiological ovarian cells. In contrast, Schmitt et al [ 252 ] noted that chemerin in vitro reduced the number of cells in the OVCAR-3 line. They also noted that chemerin affected the activation of Interferon alpha (IFNα) response genes, mainly Interferon alpha-inducible protein 27 (IFI27), 2′-5′-Oligoadenylate Synthetase 1 (OAS1), Interferon Induced Protein With Tetratricopeptide Repeats 1 (IFIT1) and Interferon Regulatory Factor 9 (IRF9), and thus affected IFNα activity.…”
Section: Chemerinmentioning
confidence: 95%
“…They found that body-fat mass appears to be the main determinant of increased chemerin and decreased omentin levels in women with PCOS [105]. Schmitt M. et al [106] studied the effect of chemerin on ovarian cancer cell lines in vitro. The addition of chemerin significantly reduced the number of OVCAR-3 cells and halved the colony growth of these cells.…”
Section: Chemerinmentioning
confidence: 99%